ESTABLISHMENT OF THE ARMY RAIDER UNIT ORGANIZATION IN COUNTER-TERRORISM - harto, Sugi; yadi, Mul; Arfina Sukabdi, Zora (UI Scholars Hub, 2021)
Terrorism in Indonesia is a threat to security and can threaten the existence of a country so that the involvement of the military is justified in handling it according to the mandate of the law. Currently, the role of handling terrorism by the military is carried out by a special unit, the army also has a Raider unit which was deployed in Kotama and is considered an organization that can tackle terrorism. The formation of the Raider Unit organization in countering terrorism, especially the action against terrorism is influenced by aspects of human resources, organizational structure, and working relations as well as organizational leadership. In the implementation of counter-terrorism, the Battalion Raider uses the capability of destruction raid and liberation raid in military operations other than war (OMSP) where its use will be held in the relationship of a team or task force that has been given special capabilities and skills to paralyze and dismantle terrorist networks. With the assignment of Battalion Raider for counter-terrorism, a strategy is required to ensure that the main task is completed optimally, including by optimizing existing human resources to complete the task.